Proposal 3E analysis and multi-objective optimization of a new biomass-based energy system based on the organic cycle and ejector for the generation of sustainable power, heat, and cold. (October 2022) - Hai, Tao; Dhahad, Hayder A.; ATTIA, El-Awady; Fareed Ibrahim, Banar; Mohamed, Abdullah; Fahad Almojil, Sattam; Ibrahim Almohana, Abdulaziz; Fahmi Alali, Abdulrhman; Farhang, Babak
Highlights: A new system is proposed based on biomass fuel and ejector-based organic flash cycle. The ANN and TOPSIS method is used to find the optimum working conditions. Optimization results indicate that, at the optimal point, net power output, cost rate, and pollution becomes 10281 kW, 142.54 $/hr, and 0.53 kg/kWh, respectively. Abstract: It has long been proven that biomass energy may be used to convert chemical energy into electricity, heating, and cooling on a sustainable basis. It emits less pollution, has a greater heat source temperature, and is compatible with various energy systems. The chemical energy contained in biomass is exploited to create heating, cooling, and electricity in this research using efficient ejector-based-organic cycles. The system comprises three distinct subsystems; the gasification process, an externally fueled gas turbine that serves as the system's primary mover and upper cycle, and an organic flash cycle with an ejector. The exit hot gases are then utilized to heat a steam Rankine cycle, the condenser of which is the ejector-based-organic cycle's evaporator. ANN and TOPSIS techniques are used to undertake the 3E analysis, parametric research, and multi-criteria optimization. The findings reveal that biomass characteristics have a measurable impact on system performance. Additionally, the optimization findings indicated that at the optimal point, the energy efficiency, cost rate, CO2 emission, and net power production are 24.07 %, 142.54 $/hr, 0.53 kg/kWh, and 10281 kW, respectively.